Supervisi Akademik Berorientasi Coaching dan Mentoring: Telaah Sistematis Terhadap Efektivitas dan Implementasi di Sekolah - Deti Harlena (Journal of Innovation in Teaching and Instructional Media, 2025)
Academic supervision based on coaching and mentoring is an approach that school principals can use to enhance teachers’ performance as instructional leaders. However, its implementation remains limited due to a lack of understanding regarding its effectiveness, practical application, and impact on learning quality. This study aims to provide insights for principals and teachers through a Systematic Literature Review (SLR) of 15 selected articles from indexed journals published in the last 10 years, both in educational and non-educational (corporate) settings. The analysis reveals that this approach effectively improves teachers’ professional and pedagogical competencies, fosters reflective practices, and builds a collaborative school culture. Furthermore, it enhances teachers’ self-confidence, encouraging greater creativity and innovation in teaching.